2022
DOI: 10.1371/journal.pone.0258054
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibitors therapy protects glucotoxicity-induced β-cell failure in a mouse model of human KATP-induced diabetes through mitigation of oxidative and ER stress

Abstract: Progressive loss of pancreatic β-cell functional mass and anti-diabetic drug responsivity are classic findings in diabetes, frequently attributed to compensatory insulin hypersecretion and β-cell exhaustion. However, loss of β-cell mass and identity still occurs in mouse models of human KATP-gain-of-function induced Neonatal Diabetes Mellitus (NDM), in the absence of insulin secretion. Here we studied the temporal progression and mechanisms underlying glucotoxicity-induced loss of functional β-cell mass in NDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…Human and rodent studies have demonstrated improvements in β-cell function following treatment with SGLT2i in vivo, which has been linked mechanistically to improved glucotoxicity [32][33][34][35][36][37]. However, it is not clear whether this reflects protection of individual β-cells against progressive β-cell decline in T2D or a compensatory response to the favorable metabolic milieu in vivo following SGLT2i therapy.…”
Section: Sglt2i Improves In Vivo β-Cell Function In Dio Micementioning
confidence: 99%
“…Human and rodent studies have demonstrated improvements in β-cell function following treatment with SGLT2i in vivo, which has been linked mechanistically to improved glucotoxicity [32][33][34][35][36][37]. However, it is not clear whether this reflects protection of individual β-cells against progressive β-cell decline in T2D or a compensatory response to the favorable metabolic milieu in vivo following SGLT2i therapy.…”
Section: Sglt2i Improves In Vivo β-Cell Function In Dio Micementioning
confidence: 99%
“…Shyr et al (24) revealed that treatment with the SGLT2 inhibitor dapagliflozin restored insulin content, decreased proinsulin : insulin ratio and reduced oxidative and endoplasmic reticulum stress. Their data from mouse models demonstrate that: i) hyperglycemia per se, and not insulin hypersecretion, drives β-cell failure in diabetes, ii) recovery of β-cell function by SGLT2 inhibitors is potentially through reduction of oxidative and ER stress, iii) SGLT2 inhibitors revert/prevent β-cell failure when used in early stages of diabetes, but not when loss of β-cell mass/identity already occurred, iv) common execution pathways may underlie loss and recovery of β-cell function in different forms of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond their potent glucose-lowering effects, they have other pharmacological effects such as glycogenesis suppression, improvement in the insulin sensitivity of peripheral tissues, enhancing the glucagon releasing response, and the induction of insulin secretion from pancreatic β cells [ 25 , 26 , 27 , 28 ]. Canagliflozin, dapagliflozin, and empagliflozin are well-known SGLT2 inhibitors with these effects [ 29 , 30 , 31 ]. However, they also have some adverse effects (e.g., dehydration, dizziness, hypotension, genital infections, and fainting) [ 29 ].…”
Section: Sodium-glucose Cotransporter-2 Inhibitorsmentioning
confidence: 99%
“…Kroon et al [ 89 ] demonstrated that 4 weeks of dapagliflozin therapy was associated with increased circulating levels of FFAs and enhanced hepatic FFA oxidation and ketone body formation in rats. Although some studies have reported no significant effects on lipid metabolism for these drugs [ 31 ], or have demonstrated that they may reduce FFA oxidation in high-fat diets (to prevent subsequent injury due to high lipid utilization) [ 90 ], most studies have suggested that SGLT2 inhibition prevents FFA from accumulating in adipose tissue and directs them toward oxidation and utilization to provide the needed energy in the shortage of available carbohydrates (due to glycosuria) [ 68 ]. However, the effects of these drugs on enzymes involved in FFA oxidation (e.g., acyl-CoA dehydrogenase, enoyl-CoA hydratase, hydroxyacyl-CoA dehydrogenase, and ketoacyl-CoA thiolase) [ 91 ] have not been thoroughly investigated, which need further studies.…”
Section: Sglt2 Inhibitors and Lipid Metabolismmentioning
confidence: 99%